LOAD BALANCE PCC AND FAILOVER WITH RECURSIVE GATEWAY - Deval Gusrion; Rima Liana Gema; Silky Safira; Aulia Fitrul Hadi; Silfia Andini (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
The continuous flow of information has become a necessity for organizations. The internet moves information quickly to support the activities of its users, PT. Graha Cipta Bangko Jaya. These organizations must keep running their business even when internet service is unavailable. There are several ways to overcome this problem, one of which is to use at least two different internet sources, which will be combined with failover techniques on the internet connection so that if one internet source is disconnected, it will be automatically transferred to another internet source. The failover technique is usually combined with the load balance technique, and there are several methods for the load balance, one of which is PCC (Per Connection Classifier). The PCC load balance and failover method are commonly used in the gateway check feature on the ip route menu. However, when implementing the gateway check feature, it can only check on the gateway device so that if there is a problem at the provider, it will not be able to be monitored by the router side. So that the router can check directly with the provider, it can add a recursive gateway technique to failover. A device that can support the above method is the Mikrotik Router. A Mikrotik router is a device or operating system specifically designed for routing in computer networks. Later the results of this research can ensure the availability of the internet within the organization and increase the operational productivity of the organization